Digital Marketing Communication, e-WOM Amplification, and Consumer Loyalty: A Mediation Analysis - Haryadi Mujianto; Septiawan Santana Kurnia; Oji Kurniadi; Anne Maryani (FAKULTAS DAKWAH UIN SALATIGA, 2026)
This study examines the mediating role of e-WOM amplification in the relationship between digital marketing communication strategies and consumer loyalty among Indonesian social media users. Using a quantitative explanatory survey design, data were collected from 180 purposively selected respondents with prior experience in online purchasing and e-WOM activities. The study employed multiple linear regression and mediation analysis using the PROCESS macro Model 4 with 5,000 bootstrapped samples. The findings reveal that digital marketing communication strategies significantly influence e-WOM amplification and consumer loyalty. Consumer engagement and user-generated content emerged as the strongest indicators within the digital communication and e-WOM dimensions. The mediation analysis confirmed that e-WOM amplification partially mediates the relationship between digital marketing communication and consumer loyalty, indicating that digital communication becomes more effective when consumers actively participate in disseminating brand-related information through social media interactions. These findings highlight the strategic importance of interactive communication, information credibility, and participatory digital engagement in strengthening long-term consumer loyalty. The study contributes theoretically by extending the conceptualization of e-WOM as an amplification mechanism within digital marketing communication and provides practical implications for companies seeking to optimize digital communication strategies in competitive online markets.